Upaya Peningkatan Prestasi Belajar Siswa pada Materi Skala dan Perbandingan Melalui Pembelajaran Snowball Throwing di SD Negeri 11 Mataram - Hidayani, Baiq Nurul (Jurnal Paedagogy, 2020)
The purpose of this study is to describe the application of the Snowball Throwing method to improve student learning achievement on scale and comparison material grade VI of SD Negeri 11 Mataram. This study uses a qualitative approach to the type of classroom action research. This research was conducted in two cycles which in one cycle were divided into two meetings. Data collection techniques used in this study were observation, interviews, and tests. Analysis of the data used in this research is descriptive data analysis. The results of this study indicate that snowball throwing learning can improve student achievement. This improvement in learning achievement can be seen from the increase in student scores starting from the pre-action initial test with the student completeness action 36.36% and after learning Snowball throwing the student completeness reaches 70.45% for the first cycle post test and 77.27% for the post test cycle II. So it can be concluded that student achievement on scale and comparison material in class VI SD Negeri 11 Mataram can be improved by implementing Snowball throwing learning.